Field assessment of soil biological and chemical quality in response to crop management practices - Vargas Gil, Silvina; Meriles, José Manuel; Conforto, Erica Cinthia; Figoni, Gervasio Jose; Basanta, Maria; Lovera, Edgar Francisco; March, Guillermo Juan (Springer, 2021)
Soil microbiological and chemical aspects were evaluated to determine the effects of conservation tillage and crop rotation on soil fertility over a 16-year period. A field trial was established to compare two cropping systems (continuous soybean and maize/soybean, soybean/maize rotation). In addition, maize (Zea mays L.) and soybean (Glycine max L., Merr) were grown in two different tillage systems: no tillage and reduced tillage. Soil populations of Trichoderma spp., Gliocladium spp. and total fungi were more abundant when maize or soybean were under conservation tillage and in the maize/soybean and soybean/maize rotation, than in continuous soybean. Furthermore, higher levels of microbial respiration and fluorescein diacetate hydrolysis (FDA), were recorded under no tillage systems. However, soil counts of Actinomycetes and Pythium spp., and Pythium diversity together with soil microbial biomass were not affected by the field treatments. To establish a correlation with soil biological factors, soil chemical parameters, such as pH, organic matter content, total N, electrical conductivity, N–NO3 − and P were also quantified, most of the correlations being significantly positive. Under no tillage there was a clear increase of the amount of crop residues and the C and N soil content due to the presence of residues. Also the distribution of crop residues in surface soil due to zero tillage and the quality of these residues, depending on the crop rotation employed, improved on soil biological and chemical characteristics. Crop yield was also enhanced by zero tillage through the management of residues. Although yield values were not directly associated with the development of microorganisms, both yield and microorganisms were influenced by crop management. These results suggest that measuring soil properties over a long period helps to define effective management strategies in order to preserve soil conditions.